2021
DOI: 10.1002/kjm2.12478
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_0023404 serves as a miR‐636 sponge to promote malignant behaviors in cervical cancer cells through upregulation of CYP2S1

Abstract: Cervical cancer is the most common malignant gynecological tumor. Circular RNA (circRNA) circ_0023404 is reported to be upregulated in cervical cancer cells. This aim is to explore the role and mechanism of circ_0023404 in cervical cancer. circ_0023404, microRNA‐636 (miR‐636), and cytochrome P450 2S1 (CYP2S1) levels were detected by real‐time quantitative polymerase chain reaction (RT‐qPCR). Cell proliferation, migration, invasion, and apoptosis were detected by 3‐(4,5‐dimethyl‐2‐thiazolyl)‐2,5‐diphenyl‐2‐H‐te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In further assessment of the effect of this circRNA on malignant characteristics of CC, in vitro hsa_circ_0023404 sponged miR-636 which allowed for increased expression of protein coding gene target CYP2S1. This hsa_circ_0023494/miR-636/CYPS21 axis resulted in downstream malignant phenotypes including increased proliferation, migration, invasion, and decrease in apoptosis [135]. Together, these data suggest hsa_circ_0023404 as a potential target in CC therapy.…”
Section: Role Of Hsa_circ_0023404 In Cervical Cancermentioning
confidence: 81%
“…In further assessment of the effect of this circRNA on malignant characteristics of CC, in vitro hsa_circ_0023404 sponged miR-636 which allowed for increased expression of protein coding gene target CYP2S1. This hsa_circ_0023494/miR-636/CYPS21 axis resulted in downstream malignant phenotypes including increased proliferation, migration, invasion, and decrease in apoptosis [135]. Together, these data suggest hsa_circ_0023404 as a potential target in CC therapy.…”
Section: Role Of Hsa_circ_0023404 In Cervical Cancermentioning
confidence: 81%
“…Another example is bta-miR-26a which also reduced the abundance of PCK1 [44,45]. Moreover, the oncosuppressor miR-20a-3p was identified in melanoma, tongue squamous cell carcinoma, and hepatocellular carcinoma, and the oncosuppressor miR-636 was also identified in lung cancer, nasopharyngeal carcinoma, cervical cancer, endometrial cancer, ovarian cancer, and hepatocellular carcinoma [46][47][48][49][50][51][52][53][54][55][56]. It was reported that high miR-20a-3p and miR-636 expression were correlated with poor OS of CRC patients and this was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%